Real-time multimedia scheduling policies for end-to-end delay jitter and loss guarantees across ATM satellite systems. - Le Pocher, H.
We propose a simple first-in first-out (FIFO)-based service protocol which is appropriate for a multimedia ATM satellite system. The main area of interest is to provide real-time traffic with upper bounds on the end-to-end delay, jitter, and loss experienced at various service queues within a satellite network. Various service protocols, each based on a common underlying strategy, are developed in light of the requirements and limitations imposed at each of the satellite's subsystems. These subsystems include the uplink (UL) earth station (ES) service queue, on-board processing (OBP) queues, and the downlink (DL) ES service queue feeding into a wireline ATM network or directly to an end-user application. Numerous network simulation results demonstrate the tractability, efficiency, and versatility of the underlying service discipline. Key features of our strategy are its algorithmic and architectural simplicity, its non-ad-hoc scheduling approach, and its unified treatment of all real-time streams at all service queues. In addition, the delay and jitter bounds are uncoupled. In this way, end-to-end jitter can be tightly controlled even if medium access requires long indeterminate waiting durations
Keywords: FIFO; QoS; Delay bound; Delayed frame queueing protocol; Downlink; Efficiency; End-to-end delay jitter; First-in first-out based service protocol; Jitter bound; Loss guarantees; Multimedia ATM satellite system; Network simulation results; On-board processing queues; Real-time multimedia scheduling; Satellite subsystems; Service queue; Uplink earth station; Wireline ATM network